2012
DOI: 10.1080/13504851.2011.566170
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Chinese enterprises: Does human resource management matter?

Abstract: Data Envelopment Analysis (DEA) was applied to Chinese enterprises with different forms of ownership to estimate their efficiency. The efficiency scores obtained were further regressed against scores rating the implementation of Strategic Human Resource Management (SHRM) and other explanatory data. State-Owned Enterprises (SOEs) were the least efficient, whereas foreign-owned firms were the most efficient. Tentative evidence was found of a relationship between SHRM practices and enterprise efficiency, but only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Here, we use only two variants of the POLCON variable, POLCON and POLCON% since POLCON þ was found not to be significant in previous regression. Table V shows that after controlling for other factors, politically connected firms that have a central-government ownership have the largest positive effect (0.013 in Model 1) on overinvestment, which is significant at the 1 percent level, as compared to those for Corporate overinvestment non-SOEs and local-SOE, a result consistent with Ng and Wei (2012) on the greater inefficiency of central-SOEs. For all types of firms, the ownership structure variable interacted with RPT and political connections have a negative effect on overinvestment.…”
Section: Corporate Overinvestmentsupporting
confidence: 63%
“…Here, we use only two variants of the POLCON variable, POLCON and POLCON% since POLCON þ was found not to be significant in previous regression. Table V shows that after controlling for other factors, politically connected firms that have a central-government ownership have the largest positive effect (0.013 in Model 1) on overinvestment, which is significant at the 1 percent level, as compared to those for Corporate overinvestment non-SOEs and local-SOE, a result consistent with Ng and Wei (2012) on the greater inefficiency of central-SOEs. For all types of firms, the ownership structure variable interacted with RPT and political connections have a negative effect on overinvestment.…”
Section: Corporate Overinvestmentsupporting
confidence: 63%
“…For example, D. Liu et al (2017) found that employee creativity does not contribute to firm innovation effectively in SOEs as compared to POEs. Likewise, Y. C. Ng and Wei (2012) research indicated that strategic HRM has no positive impact on enterprise efficiency within SOEs. The poor utilisation of human resources in SOEs may attribute to competency and attitude issues of employees.…”
Section: A More Diverse Economy With Various Challengesmentioning
confidence: 99%
“…For example, D. Liu et al (2017) found that employee creativity does not contribute to firm innovation effectively in SOEs as compared to POEs. Likewise, Y. C. Ng and Wei (2012) research indicated that strategic HRM has no positive impact on enterprise efficiency within SOEs. The poor utilisation of human resources in SOEs may attribute to competency and attitude issues of employees.…”
Section: A More Diverse Economy With Various Challengesmentioning
confidence: 99%